Effectiveness of DCT (Discrete Cosine Transform) and Walsh Transforms Employing DWT-SVD (Wavelet Transform and Singular Value Decomposition) Designed for Watermarking - Er. Kulbushan Rassewatt; Er Deepak Vatts (Journal of Applied Science, Engineering and Technology, 2025)
This work provides a color DWT-DCT-SVD-based picture watermarking method. Singular value decomposition is used to factorize each sector of each frequency sub-band after employing DCT to specified wavelet sub-bands. The watermark is integrated in the image and has the same values as the host image by altering the unique point of the cover image. The efficiency from presented strategy matched and analyzed by substituting Walsh in place of DCT within the preceding mixture. Walsh produces an approach that is statistically quick and has satisfactory accuracy. The method's imperceptibility is assessed by inserting a watermark/logo in the HH1, HL2, and HH2 frequency sub bands. Using HH1 sub-bands instead of HL2 and HH2 sub-bands to incorporate watermarks is more durable and undetectable.